KINERJA KEUANGAN LQ45 SEBELUM DAN SAAT TERJADI PANDEMI COVID-19: FINANCIAL PERFORMANCE OF LQ45 STOCKS BEFORE AND DURING THE COVID-19 PANDEMIC - Feny Maulina; Hamidah Hamidah; Destria Kurnianti (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
The purpose of this study is to analyze the financial performance of LQ45 companies before and during the coronavirus infection pandemic. The uantitative approach uses secondary for 2018-2021. Secondary data is sourced from the official website of the Indonesia Stock Exchange www.idx.co.id and LQ45 index company annual reports. The population is 20 companies included in the LQ45 index 2018-2021 period. The sampling method was purposive sampling which consisted of 80 data. Stock Price is dependent variable while CR, ROE, DER, TATO, and EPS are the independent variable. The results showed that EPS has significant positive effect on stock prices. CR, ROE, and DER do not have a significant positive effect on stock prices and ROE does not have a significantnegative effect on stock price. There is no different in the mean of the independent variables before and during the pandemic